Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

logarithm question! :)?

Simplify ln(a^2−b^2)−ln(a−b) as much as possible.

thank you!

3 Answers

Relevance
  • Rogue
    Lv 7
    7 years ago
    Favorite Answer

    ln(a^2 − b^2) − ln(a−b)

    given a^2 − b^2 = (a + b)(a − b)

    => ln((a + b)(a − b)) − ln(a − b)

    given log(n) − log(m) = log(n/m)

    => ln((a + b)(a − b)/(a − b))

    => ln(a + b) for a − b > 0

  • 7 years ago

    ln(a^2−b^2)−ln(a−b)

    = ln [ (a^2-b^2) / (a-b) ]

    = ln [ (a-b)(a+b)/(a-b) ]

    = ln (a+b)

  • 7 years ago

    ln(a^2 -b^2) - ln(a-b)

    = ln((a-b)(a+b)/(a-b))

    = ln(a+b)

Still have questions? Get your answers by asking now.